Evolution of Production Specialization and Factor Accumulation in Sub‐Saharan and North Africa - (:unkn) unknown (My University, 2025)
Despite trade liberalization and regional economic integration policies, the level of trade and specialization in Africa is stagnating. This long‐term observation contrasts with recent developments in Africa since the 2000s. This study aims to assess how changes in factor endowments affect the specialization pattern of production, exploring the underlying neoclassical determinants. We used a global panel dataset of six industries belonging to 25 sub‐Saharan and North African countries from 1980 to 2019 to empirically investigate the impact of factor endowments on specialization in production. To achieve this, we opt for a feasible generalized least squares method and impulse response functions by using labor abundance, agricultural land abundance, and physical capital abundance as exogenous variables and the share of value added in GDP as a proxy for specialization in production. Our results show (i) a differentiated role for factors of production in specialization, (ii) that factors such as public capital and skilled human capital are still underexploited in several economic regions, (iii) a persistent specialization in primary sectors, (iv) service sectors are gradually gaining in importance, and (v) a neglect of manufacturing due to the underexploitation of public and private capital. These findings highlight the need to adopt appropriate strategies to strengthen sectoral competitiveness.
Keywords: African Research